Application of Multi-Cylinder Synchronous Control for Telescopic Mechanism of Marine Steel Pile Cleaning Equipment - Chao Li; Nan Pang; Kai Xu; Qingling Geng; Xiangyu Wang; Feihong Yun; Lei Gao (Journal of Marine Science and Engineering, 2023)
In order to clean up marine fouling attached to marine steel pile, this paper proposed an innovative configuration scheme of the marine steel pile cleaning equipment by the scraping method and its telescopic mechanism by applying a multi-cylinder synchronous control strategy to the cleaning equipment, and produced a test prototype of the cleaning equipment that could solve the problem of cleaning equipment eccentricity and tilt in the field of ocean engineering. Based on the MATLAB Simulink module, a simulation model of the operation process of the telescopic mechanism of the marine steel pile cleaning equipment was established to complete the evaluation of the multi-cylinder synchronous control performance under multiple working conditions. Through the test, the synchronous working performance of the telescopic mechanism of the cleaning equipment under the no-load condition was preliminarily verified. The test results showed that under the no-load condition, the relative errors between the three cylinders and the target displacement were 0.8%, 0.4%, and 0.2%, respectively, and the cleaning equipment could reach the specified working position at the given working speed. The displacement synchronization error between each cylinder was 0.7 mm, 0.7 mm, and 0.6 mm, respectively, and the displacement synchronization error was controlled within 1 mm. The telescopic mechanism had good synchronization, which can ensure the stability and prevent the eccentricity and tilt during the cleaning equipment operation as well as provide a valuable reference for the manufacturing of cleaning equipment.